The management of the early stages of restructuring in a tertiary-education institution: An organisational commitment perspective - C. A. Arnolds; C. Boshoff (South African Journal of Business Management, 2004)
Restructuring in business firms is often characterised by uncertainty, anxiety, low morale, tardy job performance and high levels of absenteeism and staff turnover. Restructuring has recently been extended to tertiary education, but its effects on the higher education environment have not been thoroughly investigated.This study investigates the impact of restructuring (mergers) on the organisational commitment, job performance and intent to resign of tertiary education staff, as well as the relationship between selected antecedents (commitment to top management and satisfaction with career factors, monetary remuneration, fringe benefits, relations with peers and growth needs) and organisational commitment.The results show that the respondents, during the early stages of restructuring, exhibit low levels of organisational commitment, commitment to top management and satisfaction with monetary remuneration, fringe benefits and career factors. They also report high levels of satisfaction with growth factors (opportunities for training and development), relations with peers and performance intentions, and low levels of intentions to resign.Multiple regression analyses reveal that organisational commitment is positively related to performance intentions and negatively related to intent to resign. The results also show that commitment to top management and satisfaction with fringe benefits, peer relations and career factors were positively related to organisational commitment. Neither satisfaction with monetary remuneration nor the satisfaction of growth needs was significantly related to organisational commitment. The managerial implications of these findings are discussed.
Keywords: 650